PENGARUH REGULASI EMOSI TERHADAP TINGKAT STRES AKADEMIK MAHASISWA PSIKOLOGI UNIVERSITAS NEGERI PADANG - Al Zira Sakinah; Indriany Syafitri; Nurhayati Nurhayati; Khaila Chantika Sari; Qurratu Nisaa’ Pingatian; Marsha Nafisa; Izzanil Hidayati (Cahaya Ilmu Bangsa Institute, 2025)
The main problem faced by students, especially psychology students, who are often faced with academic loads and emotional demands is academic stress. Academic stress levels can be influenced by a person's ability to control their emotions in an appropriate manner. The aim of this research is to find out how emotional regulation impacts the academic stress levels of Psychology students at Padang State University. This research uses a quantitative approach and uses a questionnaire distributed to 302 respondents. This research uses the Questionnaire of Emotion Regulation (ERQ) and the Perceived Stress Scale. According to the results of this research, there is an influence between academic stress variables and emotional regulation variables on students. The calculated F value is 5.522, with a significance level of 0.019 < 0.05. The results of this research indicate that emotional regulation is very important as a way to protect students from academic stress. This research also encourages the development of emotional regulation training programs for students. Faculty can use this information to create better methods for managing academic loads, reducing stress, and supporting student well-being.